1994
DOI: 10.1105/tpc.6.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Position Effect in Mature Transgenic Plants Conferred by the Chicken Lysozyme Matrix-Associated Region.

Abstract: Matrix-associated regions may be useful for studying the role of chromatin architecture in transgene activity of transformed plants. The chicken lysoryme A element was shown to have specific affinity for tobacco nuclear matrices, and its influence on the variability of transgene expression in tobacco plants was studied. T-DNA constructs in which this element flanked either the P-glucuronidase (GUS) reporter gene or both reporter and selection gene were introduced in tobacco. The variation in GUS gene activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(52 citation statements)
references
References 37 publications
0
52
0
Order By: Relevance
“…Cultured cells as undifferentiated cell types show relatively more uniform transcriptional activity along the entire chromosome ( Figure 6). Previous studies have shown the effect of chromatin structures on gene transcription in a wide range of plants, including monocots and dicots (Mlyná rová et al, 1994;Tikhonov et al, 2000;Rudd et al, 2004), but our data extended this possible regulation to the chromosomal scale and tentatively associated this regulation with the heterochromatin and euchromatin structures. The underlying mechanisms of those regulations are not known, but modification at the DNA or histone level or RNA interference are possible routes (Henikoff and Comai, 1998;Pandey et al, 2002;Reyes et al, 2002;Lippman and Martienssen, 2004).…”
Section: Chromosome-level Regulation Of Transcriptional Activitymentioning
confidence: 54%
“…Cultured cells as undifferentiated cell types show relatively more uniform transcriptional activity along the entire chromosome ( Figure 6). Previous studies have shown the effect of chromatin structures on gene transcription in a wide range of plants, including monocots and dicots (Mlyná rová et al, 1994;Tikhonov et al, 2000;Rudd et al, 2004), but our data extended this possible regulation to the chromosomal scale and tentatively associated this regulation with the heterochromatin and euchromatin structures. The underlying mechanisms of those regulations are not known, but modification at the DNA or histone level or RNA interference are possible routes (Henikoff and Comai, 1998;Pandey et al, 2002;Reyes et al, 2002;Lippman and Martienssen, 2004).…”
Section: Chromosome-level Regulation Of Transcriptional Activitymentioning
confidence: 54%
“…MARs are DNA sequences that are thought to mediate the binding of chromatin to the proteinaceous nuclear matrix, thereby creating chromatin domains as topologically isolated units of gene regulation (Bode et al, 1995(Bode et al, , 1996. The presence of the chicken lysozyme MAR element known as the A element around transgenes in tobacco results in the position-independent expression of the transgenes (Mlynarova et al, 1994(Mlynarova et al, , 1995Jansen et al, 2002). This fact establishes the A element as a functional chromatin boundary, as defined by Udvardy (1999), in plants as it is in other systems (Bode et al, 1995;Strätling and Yu, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is known also for other (e.g. constitutive) promoters that individual lines transgenic for genes under control of these promoters may vary significantly in levels of expression (Peach and Velten, 1991;Mlynarova et al, 1994). When using a pathogen-inducible promoter-dependent strategy, the ability to make sufficient well-responding lines may pose limitations on the applicability of the promoter.…”
Section: Introductionmentioning
confidence: 99%